(untitled) (Annals of Medical Research, 2023)
Aim: In this study, the functional results of patients with femoral intertrochanteric fractures who underwent surgery were compared with their clinical features in terms of proximal femoral nail ( PFN ) and bipolar hemiarthroplasty ( BPH ). Materials and Methods: PFN (Group 1) was implanted in 40 of 89 patients (44 female, 45 male) aged between 51-80 (mean 68,16 ± 6,78) whereas BPH (Group 2) was used with 49 patients. Age, gender, fracture mechanism, additional disease, Body mass index (BMI), Albumin level, Hemoglobin (Hb) decrease level, T-score, American Society of Anesthesiologists (ASA) classification, type of anesthesia, surgery type, operation time, hospital stay and full weight-bearing time, the scores of Harris Hip Function (HHS), the social function of Jensen (JSF), Parker-Palmer mobility (PPMS) in preoperative and postoperative periods, and postoperative complications were all recorded. Results: In group 1; patients were younger, operation time was 46.78 ± 5.29 minutes and hospital stay was 2.48±0.75 days, which were shorter compared with group 2. For group 1, most surgery types were closed, T-score was -2.49±0.59 and better, the time of full weight-bearing was 3.48±0.78 months, Hb decrease was 1.17±0.37 and less, and Albumin level was 3.11±0.4 g/dL and higher compared to group 2 (p<0.05). HHS was better in the BPH group at the sixth month (p<0.05). In group 1, the 12th, and 24th months scores of JSF were better, PPMS was higher in all evaluations (p<0.05). Operation time, ASA, T-score, and albumin levels correlate with functional scores, while BMI and Hb did not. Conclusion: Many factors are important for progressing patients with intertrochanteric femur fractures toward a functional level. Considering these parameters in patients with femoral intertrochanteric fracture, PFN or BPH can both be used for treatment according to the surgeon’s preference.